2020
DOI: 10.1371/journal.pone.0237267
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ demographic and socioeconomic characteristics influence the therapeutic decision-making process in psoriasis

Abstract: Background Knowledge regarding differences in care for psoriatic patients is limited. The aim of this study was to investigate factors influencing prescription of systemic treatments for patients with psoriasis with a special focus on socioeconomic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Due to limited capture of socioeconomic data, we were unable to fully adjust for this confounder in the analysis, however we did identify that household density was inversely associated with shielding. Both shielding behaviour and clinical decision making around systemic therapies globally (including access to medications) may be influenced by socioeconomic variables such as income and education 31,32 , which may in turn influence outcome of COVID-19 4 . Linkage between health, social, behavioural and employment data should thus be prioritised in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Due to limited capture of socioeconomic data, we were unable to fully adjust for this confounder in the analysis, however we did identify that household density was inversely associated with shielding. Both shielding behaviour and clinical decision making around systemic therapies globally (including access to medications) may be influenced by socioeconomic variables such as income and education 31,32 , which may in turn influence outcome of COVID-19 4 . Linkage between health, social, behavioural and employment data should thus be prioritised in future research.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Notably, a recent Italian study showed that women were less likely to receive biologics than men. 12 Two-thirds of the patients already had at least one child. The majority of those without children were rather confident about the outcome of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“… 9 – 11 Notably, a recent Italian study showed that women were less likely to receive biologics than men. 12 …”
Section: Discussionmentioning
confidence: 99%
“…5,6 It is known that infections, 6 psychological stress, 6 diet, 6,7 medication, 6,7 smoking, [6][7][8][9][10] alcohol drinking, 6,9,11 so as the cold and dry weather, 12 could trigger the flare-ups of psoriasis. Systemic inflammation together with demographics 13 could drastically influence the prescription of treatment and therapeutic response by increasing psoriasis-related comorbidities burden (ie, cardiovascular, 14 respiratory 15 or hepatic disease 16 ). Previous studies confirmed that psoriasis conditions vary with the season, and severe psoriasis were more likely to happen in cold season, such as autumn or/and winter.…”
Section: Introductionmentioning
confidence: 99%